Metal Craft Studio Development: An Idea to Prepare a Teaching Factory Education Concept Model in the Craft Education Study Program, Yogyakarta State University - Iswahyudi Iswahyudi (Randwick International of Education and Linguistics Science Journal, 2021)
This study aims to prepare a model for the development of a metal craft practice studio which includes space, equipment, maintenance and occupational safety and health. This study uses a qualitative method with research locations in the metal craft studio at P4TK, Vocational High School 5 Yogyakarta, BRTPD Bantul, and the Indonesian Institute of the Arts Surakarta. Research time March-July 2018. Research instruments are interview, observation, and documentation guidelines. The validity of the data used the validity of interview data, observation, and documentation. Data analysis of data collection, data display, data reduction, and drawing conclusions. The expected result of the research is the realization of a Craft Education studio that is representative and relevant to the world of vocational education and the world of the craft industry. The development of Kriya educational studios refers to existing studios in training institutions and vocational schools. The expected product is the formulation of the Craft Education studio as a studio learning guide. The realization of a studio arrangement that makes it easy for users to produce and manage craft studios. The results of this studio research are expected to be used for the development of the Craft Education studio, Faculty of Language and Arts, Yogyakarta State University.